2006
DOI: 10.1007/s10162-005-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Loudness Adaptation in Acoustic and Electric Hearing

Abstract: The present study is aimed to evaluate and compare loudness adaptation between normal hearing and cochlear-implant subjects. Loudness adaptation for 367-s pure tones was measured in five normal-hearing subjects at three frequencies (125, 1,000, and 8,000 Hz) and three levels (30, 60, and 90 dB SPL). In addition, loudness adaptation for 367-s pulse trains was measured in five Clarion cochlear-implant subjects at three stimulation rates (100, 991, and 4,296 Hz), three levels (10, 50, and 90% of the electric dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…This occurred most often during high rate stimuli, creating an overall sound environment that was quieter than his tinnitus alone. The phenomenon of adaption of signal with increasing frequency and decreasing loudness level despite rate, place and mode of stimulation has previously been described 5 . The subject also defined each successful stimulus as more pleasant in quality than his tinnitus that was being replaced, regardless of whether the stimulus was administered at a high or low rate.…”
Section: Discussionmentioning
confidence: 97%
“…This occurred most often during high rate stimuli, creating an overall sound environment that was quieter than his tinnitus alone. The phenomenon of adaption of signal with increasing frequency and decreasing loudness level despite rate, place and mode of stimulation has previously been described 5 . The subject also defined each successful stimulus as more pleasant in quality than his tinnitus that was being replaced, regardless of whether the stimulus was administered at a high or low rate.…”
Section: Discussionmentioning
confidence: 97%
“…(1), L t is the estimated loudness at time t and L 0 is the estimated initial loudness (Tang et al, 2006;Wynne et al, 2013). Using this normalization, a value of À100% corresponded to an inaudible sound, 0% corresponded to no change in loudness, and positive numbers indicated that the sound became louder over time.…”
Section: A Methodsmentioning
confidence: 99%
“…(2), y(t) is the amount of adaptation at time t, s is an asymptotic saturation value representing the amount of adaptation to an infinitely long stimulus, and s is a "time constant" representing the amount of time required to reach 63% of the asymptotic saturation value (Tang et al, 2006;Wynne et al, 2013). The saturation value was constrained to be between À100% and 0%, and the time constant was constrained to be between 0 and 180 s. Analysis of variance was used to investigate the effects of time and modulation frequency on the normalized loudness estimates.…”
Section: A Methodsmentioning
confidence: 99%
See 2 more Smart Citations